Personal Peacefulness and Griefing as Toxic Behavior in Online Game Players - Sahril Buchori; Nurfitriany Fakhri (Universitas Negeri Makassar, 2023)
The objective of this study is to examine the impact of personal peacefulness and disruptive behavior on individuals engaged in online gaming. Personal peacefulness refers to an individual's tranquil disposition, characterized by an inward sense of serenity. This state of being fosters an environment of non-violence and harmony, continually manifesting in many life circumstances. Griefing within the context of online gaming refers to the manifestation of antisocial conduct exhibited by gamers towards their counterparts on the same gaming platform, with the primary objective of deriving personal gratification. The participants in this study consisted of a sample size of 351 individuals who were engaged in online gaming. The data collection process involved the utilization of two distinct scales: the Self-Perception Scale (SPS) for measuring Intrapersonal Peace, which had 12 statement items, and the Grief Play Scale, which consisted of 32 statement items. The findings obtained from the application of Spearman Rho Analysis to the data indicate that the significant value, denoted as p, is equal to 0.01, which is less than the predetermined threshold of 0.05. Consequently, the hypothesis formulated for this study is determined to be accepted. It can be inferred that a significant correlation exists between an individual's personal peacefulness and engagement in griefing behavior.